Study Energy Consumption and Potential Saving At The Recycle Factory - Noranai, Zamri; Ab.Ghani, Syuib (Research Progress in Mechanical and Manufacturing Engineering, 2023)
The effects of various methods used to recycle Polyethylene, the temperature required during recycling, the time required for the Polyethylene to be completely recycled, and the energy required to recycle the materials and reduce waste, such as heat dissipated. To make high-quality, long-lasting products. Some of the collected trash didn't belong. The study aims to discover the plastic recycling process, improve it, and cut energy costs. There are several recyclable plastics today. This study examines LDPE (LDPE). In Perak's Kinta Recycle and Recovery Factory. This study examines techniques to reduce energy use during factory recycling. It will go into detail on recycling plastic because different elements must be separated before recycling and there are many types of recyclable plastic. This research will help in the development and testing of recycled plastic. This investigation could determine which method and machine work best under given situations. It would help comprehend the recycling method, staging, and manufacturing's effect on the factor. Define the basic technique for recycling Low Density Polyethylene to increase machine energy efficiency. This research will show us why recycling is essential